مكانة المعارف التقليدية في منظومة الملكية الفكرية - أيت تفاتي، حفيظة Ait Tafati, Hafizah (جامعة زيان عاشور بالجلفة, 2021)
المعارف التقليدية جزء لا يتجزأ من المنظومة التراثية للشعوب التي تمتلكها، لكنها تتميز بمجموعة من الخصائص عن باقي المكونات التراثية الأخرى، فهي غالباً ما تنتج عن إبداع جماعي ولا تزال تحافظ على صلتها بالجماعة التي أبدعتها. ونظراً لقيمة هذه المعارف المعنوية والاقتصادية وحتى العلمية، تسعى المجتمعات المالكة لها حالياً للمطالبة بسن تشريعات وطنية وإقرار صكوك دولية لحمايتها كفئة من فئات حقوق الملكية الفكرية، إلا أن خصوصية المعارف التقليدية عن باقي الحقوق الفكرية تتطلب إعادة تكييف المبادئ والأحكام التي يقوم عليها نظام هذه الحقوق لتتماشى مع طبيعة هذه المعارف الجماعية والمؤبدة، وتستجيب لمطالب المجتمعات المالكة لها في نسبتها إليهم ومشاركتهم الكاملة في القرارات المتعلقة بالنفاذ إلى معارفهم واستخدامها والحصول على جزء من المنافع التي تعود من هذا الاستخدام. وهو ما لا يمكن تحقيقه إلا بتحديد المقصود بهذه المعارف وجوانب اختلافها مع حقوق الملكية الفكرية الأخرى.
Traditional knowledge is an integral part of the heritage of the peoples who own it, but it is distinguished by a set of characteristics from other heritage elements, as it is often the result of collective creativity and always maintains its connection with this group. and taking into account the value of this moral, economic and even scientific knowledge, the companies owners seek their protection by the enactment of adequate legal texts in order to protect them as a category of intellectual property rights, and to unify international efforts for the adoption of a protection instrument within the intellectual property system. However, the confidentiality of traditional knowledge with respect to the rest of intellectual rights requires a readjustment of the principles and provisions on which this system is based, to be in line with the nature of this collective and permanent knowledge, and to meet the requirements of its proprietary companies as to their attribution and their full participation in decisions relating to the access and use of their knowledge and the obtaining of part of the resulting benefits. It requires the introduction of this knowledge and how it differs from other property rights.
Keywords: التراث الثقافي -- الملكية الفكرية -- الحماية الدولية -- القوانين والتشريعات